Screening of Oil Palm Varieties Resistant against the Leaf Spot Disease Caused by Curvularia oryzae Bugnic - Jittra Kittimorakul (Prince of Songkla University, 2024)
Thesis (Ph.D., Plant Science)--Prince of Songkla University, 2019